Prevalence of Postpartum Family Planning Service Coverage in Selected Referral Facilities of Nepal - Thapa, Kusum (JNMA J Nepal Med Assoc, 2020)
INTRODUCTION: Nepal Society of Obstetricians and Gynecologists jointly with the Nepalese government and with the support from the International Federation of Obstetrics and Gynecology has implemented an initiative to institutionalize postpartum family planning services in selected major referral facilities of Nepal to address the gap of low uptake of postpartum family planning in Nepal. The aim of the study is to find the prevalence of the service coverage of postpartum contraception in the selected facilities. METHODS: A descriptive cross-sectional study was conducted in seven major referral facilities across Nepal. Data were collected from the hospital records of all women who delivered in these facilities between October 2018 and March 2019. Ethical approval for this study was obtained from Nepal Health Research Council. Data analysis was done with SPSS version 23. RESULTS: Among the 29,072 deliveries from all the facilities, postpartum family planning counseling coverage was 27,301 (93.9%). The prevalence of uptake of Postpartum Intrauterine Device is 1581 (5.4%) and female sterilization is 1830 (6.3%). In total 11387 mothers (52.2%) had the intention to choose a postpartum family planning method. However, 36% of mothers neither used nor had the intention to choose a postpartum family planning method. CONCLUSIONS: The coverage of Postpartum Intrauterine Device counseling service coverage in Nepal is higher in 2018 as compared to 2016-2017 and in other countries implementing Postpartum Intrauterine Device initiatives. However, the prevalence of service coverage of immediate Postpartum Family Planning methods, mainly Postpartum Intrauterine Device in 2018 is lower in Nepal as compared to 2016-2017, and other countries implementing Postpartum Intrauterine Device initiative. More efforts are needed to encourage mothers delivering in the facilities to use the postpartum family planning method.